Developing Of Writing Paragraph Materials By Using Argumentative Text At The Eight Grade Student's Of Madrasah Tsanawiyah Negri 4 Mandailing Natal - Megasari Megasari; Ahmad Laut Hasibuan (Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to determine the development, validity and effectiveness of the development of Writing Paragraph Materials By Using Argumentative Text at The Eight Grade Student's of Madrasah Tsanawiyah Negri 4 Mandailing Natal. This research is a research and development (R&D) using the Sugiyono model. The instrument used is a questionnaire for expert lecturers and students, interviews with teachers, and the results of the last test given to students. The test results from the validator through media design aspects of 100% in the very good category and 90.83% from material experts I and II in the very good category, so this product was declared worthy of being used as learning so that students were more active in participating in learning.And the test results show that the average value of students gets an average of 61.76% so that they get the effective criteria. The effectiveness of the product can be seen from the results. Based on the results, the student response when using the product was very good. The results of the responses of students who answered